2014 IEEE Conference on Computer Vision and Pattern Recognition 2014
DOI: 10.1109/cvpr.2014.75
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Localization and Pose Estimation for Large 3D Models

Abstract: We consider the problem of localizing a novel image in a large 3D model. In principle, this is just an instance of camera pose estimation, but the scale introduces some challenging problems. For one, it makes the correspondence problem very difficult and it is likely that there will be a significant rate of outliers to handle. In this paper we use recent theoretical as well as technical advances to tackle these problems. Many modern cameras and phones have gravitational sensors that allow us to reduce the sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 28 publications
0
74
0
Order By: Relevance
“…Using a finer vocabulary can reduce the problem of voting for unrelated images [22,43,47]. Yet, most large-scale localization approaches rely on directly matching the feature descriptors against the landmark descriptors without any intermediate retrieval step [25,26,41,42,49]. A popular approach to accelerate the matching process is to build a kd-tree for (approximate) nearest neighbor search on top of the landmark descriptors [25,49].…”
Section: Localization Against the Global Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Using a finer vocabulary can reduce the problem of voting for unrelated images [22,43,47]. Yet, most large-scale localization approaches rely on directly matching the feature descriptors against the landmark descriptors without any intermediate retrieval step [25,26,41,42,49]. A popular approach to accelerate the matching process is to build a kd-tree for (approximate) nearest neighbor search on top of the landmark descriptors [25,49].…”
Section: Localization Against the Global Modelmentioning
confidence: 99%
“…Yet, most large-scale localization approaches rely on directly matching the feature descriptors against the landmark descriptors without any intermediate retrieval step [25,26,41,42,49]. A popular approach to accelerate the matching process is to build a kd-tree for (approximate) nearest neighbor search on top of the landmark descriptors [25,49]. While offering an excellent search performance, a kdtree is rather slow due to backtracking and irregular memory access [41].…”
Section: Localization Against the Global Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, if the number of points is very large, the outlier rejection scheme can become extremely slow. Recently, [23] has shown that priors about the orientation of the camera relative to the ground plane can speed up this process. We do not consider these kind of priors for our method, though.…”
Section: Related Workmentioning
confidence: 99%
“…Using two matching MSER feature points, an approximate fundamental matrix could be estimated. Lately, methods that optimally find models that maximize the number of inliers, in polynomial time, have been developed, [5,25]. We will in this paper investigate a number of specific geometric problems that have received little or no attention earlier, related to orthographic projections of rigid scenes in two views.…”
Section: Introductionmentioning
confidence: 99%